Yolk–Shell‐Structured Cu/Fe@γ‐Fe2O3 Nanoparticles Loaded Graphitic Porous Carbon for the Oxygen Reduction Reaction. (3rd August 2017) - Wang, Meiwen; Su, Chao; Saunders, Martin; Liang, Ji; Shao, Zongping; Wang, Shaobin; Liu, Jian
Abstract: Core–shell Cu/γ‐Fe2 O3 @C and yolk–shell‐structured Cu/Fe@γ‐Fe2 O3 @C particles are prepared by a facile synthesis method using copper oxide as template particles, resorcinol‐formaldehyde as the carbon precursor, and iron nitrate solution as the iron source via pyrolysis. With increasing carbonization temperature and time, solid γ‐Fe2 O3 cores are formed and then transformed into Fe@γ‐Fe2 O3 yolk–shell‐structured particles via Ostwald ripening under nitrogen gas flow. The composition variations are studied, and the formation mechanism is proposed for the generation of the hollow and yolk–shell‐structured metal and metal oxides. Moreover, highly graphitic carbons can be obtained by etching the metal and metal oxide nanoparticles through an acid treatment. The electrocatalytic activity for oxygen reduction reaction is investigated on Cu/γ‐Fe2 O3 @C, Cu/Fe@γ‐Fe2 O3 @C, and graphitic carbons, indicating comparable or even superior performance to other Fe‐based nanocatalysts. Abstract : Single‐iron yolk enclosed inside a copper‐doped gamma iron oxide shell nanoparticles encapsulated within graphitic carbon outer shell (Cu/Fe@γ‐Fe2 O3 @C) is prepared via a facile synthetic method. Yolk–shell structure is formed during the carbonization process under nitrogen gas environment without involving any templates or etchants. Such particles are tested in oxygen reduction reaction and believed to have great potentials in other energy‐related applications.